STATISTICAL ANALYSIS OF RESEARCH AND DEVELOPMENT COSTS IN THE REGIONS OF THE RUSSIAN FEDERATION - M. Efimova; E. Dolgikh (Вестник университета)
The structure and dynamics of internal costs of research and development in the regions of the Russian Federation have been considered. Particular attention has been paid to the characteristics of the scope of variation and uniformity of internal costs of research and development per organization. The regions with the maximum values of the considered indicator have been selected. The grouping of the subjects of the Russian Federation on the priority areas of research and development costs for 2010 and 2017 has been carried out. The characteristic of changes in priorities in the regions has been given.